Interpreting lime burials. A discussion in light of lime burials at St. Rombout's cemetery in Mechelen, Belgium (10th–18th centuries). (September 2015) - Schotsmans, Eline M.J.; Van de Vijver, Katrien; Wilson, Andrew S.; Castex, Dominique
Abstract: Despite the widespread use of lime in burials in varied regions throughout history, there are few documented cases of lime burials where the characteristics of the burial context, the skeletal remains and the lime inclusions have been studied in detail. The following study presents five archaeological lime burials from St. Rombout's cemetery in Mechelen, Belgium (10th–18th centuries). The findings raise several discussion points regarding the analysis and interpretation of lime burials. Lime can be present in different burial types, in single or multiple burials, in plain earth or coffin burials and with varied treatment of the human remains. Lime can have different physical appearances and vary chemically. It is not always clear how lime was applied to burials, what the intentions were and how it should be interpreted. The results of the skeletal analysis of the lime burials from Mechelen, including the demographic and paleopathological profile, combined with the study of the particular burial context and the lime component, offer important indications for interpretation. The study indicates that, whilst disease may have been one of the possible factors for the application of lime, it is likely that it was used for multiple purposes. Many questions remain unanswered. It is only by publishing more lime burials in the future and through multidisciplinary study, that those questions can be addressed.